The duration of acupuncture effects and its associated factors in chronic severe functional constipation: secondary analysis of a randomized controlled trial. (October 2019) - Wang, Yang; Liu, Yan; Zhou, Kehua; Bauer, Brent A.; Liu, Baoyan; Su, Tongsheng; Mo, Qian; Liu, Zhishun
Background: Electroacupuncture (EA) has been shown to improve complete spontaneous bowel movements (CSBMs), but the duration of its effects remains unknown. The objective of this study was to explore the duration of acupuncture effects after treatment and its associated factors for chronic severe functional constipation (CSFC). Methods: This was a secondary analysis of a multicenter, randomized, sham-acupuncture (SA) controlled trial that included 1075 participants with CSFC. The primary outcome, the duration of acupuncture effects after treatment, was the number of weeks during the 12-week follow-up period that participants were to meet the weekly CSBM responder criteria. A weekly CSBM responder was defined as a participant who had at least three CSBMs for a given week and an increase from baseline of at least one CSBM for that same week. We performed a retrospective multivariate analysis to explore potential factors associated with sustained acupuncture effects. Results: The duration of acupuncture effects in the EA group (5.5 weeks) was significantly higher than the duration of SA effects in the SA group (2.2 weeks) with a between-group difference of 3.2 weeks (95% CI, 2.77–3.78; p  < 0.001). A younger age and higher baseline CSBMs per week [regression coefficient (RC) –0.06, 95% confidence interval (CI) (−0.06 to −0.04); RC 2.43, 95% CI 1.78–3.60; respectively] were associated with longer durations of acupuncture effects. Conclusions: EA had sustained post-treatment effects for CFSC. A significant association among a younger age, higher baseline CSBMs and sustained acupuncture effects was observed. Further research is needed to confirm the association. Trial registration: ClinicalTrials.gov (NCT01726504). Registered on 26 August 2012.